Choice of treatment tactics in patients with acute diarrhea of bacterial etiology at high risk of irritable bowel syndrome - Mrs Roza Tlyustangelova; Mrs Natalia Pshenichnaya; Mrs Irina Lisinfeld; Ms Vadim Melnik (International Journal of Infectious Diseases)
Introduction: It is known that acute diarrhea, especially of bacterial etiology, can cause irritable bowel syndrome (IBS), which develops in the period of convalescence in more than 10% of cases. One of the therapeutic approaches regulating visceral hypersensitivity, which occurs in IBS, is the use of butyric acid. Purpose of the study: To provide a comprehensive assessment of the effect of calcium butyrate and inulin on reducing the risk of postinfectious IBS in patients with acute diarrhea of bacterial etiology (ADBE) with a high risk of its development in the convalescent period Materials and Methods: The study was conducted in 60 patients (ADBE) aged 18 to 60 years with a high risk of developing IBS, established on the basis of a discriminant equation including triglycerides (TG), cholesterol (CH) and urea (U) levels at the 3th day disease. YIBS=-6,441+1,065*XTG+0,197*XU+0,753*XCH. If YIBS³0,5375 the high risk of IBS is predicted (The sensitivity of the predictive model was 78.6%, the specificity - 100%). Patients were randomized into two groups: one group received conventional therapy, including probiotics, the other group additionally received Zacofalc, consisting of calcium butyrate 250 mg and inulin 250 mg (CB+I) during 30 days. The efficacy of therapy was assessed by measuring TG levels at the acute period of ADBE and at hospital discharge, fecal calprotectin and I-FABP (Intestinal fatty acid binding protein) at the acute period and one month after discharge. The data systematization and statistical processing of the results were performed using binary logistic regression and ROC analysis. The obtained differences were considered statistically significant at p < 0.05. Results: The most common pathogens of ADBE were S.enteritidis (46.7% in the group receiving CB+I and 50.0% in the group of comparison), Protei (36.7% in the group receiving CB+I and 30% in group of the comparison). Citrobacter (20% in each group). The occurrence of such representatives of opportunistic flora as campylobacter, S.typhimurium, P. aeruginosa varied from 3.3 to 13.3%. There were no statistically significant differences in the duration of the main clinical symptoms and laboratory parameters between the groups. However, fecal calprotectin and I-FABP levels decreased statistically significantly 30 days after hospital treatment in the CB+I group. Triglyceride levels were also lower during the recovery period in patients receiving CB+I. The incidence of IBS during the next 6 months of follow-up was 38.5 times lower in the CB+I group compared to patients receiving conventional therapy. Conclusions: The use of CB+I accelerates the normalization of inflammatory markers and reduces the risk of IBS development after ADBE. Therefore, CB+I may be an effective method of treatment and prevention of IBS development in patients with ADBE.